Frank Llyod Wright’s ideology towards the formation of national architectural identity in Malaysia - Ismail, Alice Sabrina; Mohd. Rasdi, Mohd. Tajudin (Fakulti Alam Bina, 2009)

(untitled)
The formation of a national identity is the core for the social, politic and economic development of a multiracial country like Malaysia. However, very little is known regarding the characteristics of architecture with a national identity since very few studies have been done. This paper is written in order to analyze the problem regarding the identity of national architecture in Malaysia and to present the results of architectural principles, which characterize the national spirit. The above problems may be solved by referring to the great master builder Frank Lloyd Wright whose philosophy is relevant with the aspiration of the masses, concerned with human values and emphasizes social culture in each of his design. Wright’s ideology and principle mentioned in this literature study consists of the understanding of ornamental elements, the usage of materials, local expression and style compositions and the designing of space articulation and form with regional appearance. All of the above may be reckoned as a guideline in order to create architecture with a national identity